The Arch of the Sergi and the Aragonese Arch - Gudelj, Jasenka (2009)
The antique Arch of Sergi has been identified as a direct model for the Renaissance Aragonese Arch in Naples. The article explores the cultural transfers and circulation of the model in the Renaissance. emulation